Newspaper clippings regarding President Cleveland’s signing of a relief bill for the estate of James C. Booth - Booth, James Curtis (1892)
Two clippings, titled "Ledger and Transcript" and "A Careful Official," document James Curtis Booth's (1810-1888) contributions to the United States Mint and announce the President's approval of an act for the relief of legal representation of Booth who lost three silver bars during his tenure.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Bills, Legislative; Clippings (Books, newspapers, etc.); Silver ingots; Cleveland, Grover, 1837-1908